Nilai-nilai dari perspektif masyarakat Melayu dalam karya agung sejarah Melayu - Mat Zin Manun (Tanjong Malim, 2009)
Nilai-nilai dari perspektif masyarakat Melayu dalam karya agung sejarah Melayu by Mat Zin Manun